Hubungan Beban Keluarga dan Keaktifan Senam dengan Kualitas Hidup Lansia di Desa Pategalan Kecamatan Jatibanteng - Ahmad Khomaedy; Ro'isah Ro'isah; Iin Aini Isnawati (Lembaga Pengembangan Kinerja Dosen, 2024)
The aging process in the elderly naturally brings physical, mental and social consequences, which affect their quality of life. This study aims to analyze the relationship between family burden and gymnastics activity with the quality of life of the elderly in Pategalan Village, Jatibanteng District. The research method used a correlational analytic design with a cross-sectional approach. The sample consisted of 109 elderly people selected by random sampling from a population of 150 people. Data collection was carried out through a questionnaire that had been tested for validity and reliability, with analysis using the Spearman Rank test. The results showed that 56% of the elderly had a good family burden, 84.4% were active in gymnastics, and 55% had a good quality of life. Spearman Rank statistical test revealed a significant relationship between family burden and gymnastics activity with the quality of life of the elderly (p-value = 0.000; p ≤ 0.005). This study confirms the importance of family support and physical activity in improving self-esteem and quality of life of the elderly. Elderly people who feel respected and have the freedom to choose for themselves tend to achieve the expected quality of life. Continuous support from family and society is the key to realizing independent and happy elderly.